Online Disinhibition dan Cyberloafing pada Pekerja (Jurnal Ilmiah Psikologi MIND SET, 2023)
Cyberloafing or the behavior of employees who carry out online activities outside of work during working hours has become commonplace over the last 20 years, and is difficult to avoid it because almost all jobs require internet access. This activity can interfere with the effectiveness of their works, but there is not much research on this, especially when it is related to online disinhibition. Online disinhibition is a psychological condition experienced by individuals who feel more comfortable doing certain behaviors online than in real life. This study aims to determine the relationship between online disinhibition and cyberloafing among employees. This research was conducted using quantitative research methods, especially correlational analysis. The measurement tools were an adaptation of the Instrument of Social Purpose Cyberloafing (Megawati, et al., 2023) to measure cyberloafing behavior and the Online Disinhibition Scale (Suler, 2004) to measure online disinhibition. Respondents in this study totaled 121 people, obtained by convenience technique sampling, in which respondents filled out a research questionnaire on the site of menelisik.id. The results obtained in this study show that there is a relationship between online disinhibition and cyberloafing among employees. Suggestion for further research to do the research to find the role of online disinhibition in cyberloafing. Applicative suggestion for company leaders to create an atmosphere that makes employees more comfortable working so as to reduce cyberloafing behavior among them.